Synthesis of a Novel 1,4-Dicarbonyl Scaffold – Ethyl 3-Formyl-4,5-dihydrofuran-2-carboxylate – and Its Application to the Synthesis of Pyridazines - Marangoni, Mário A.; Moraes, Paulo A.; Camargo, Adriano F.; Bonacorso, Helio G.; Martins, Marcos A. P.; Zanatta, Nilo (Synthesis, 2020)
The 1,4-dicarbonyl scaffold ethyl 3-formyl-4,5-dihydrofuran-2-carboxylate was obtained through the rearrangement of the parent ethyl 2-(4,5-dihydrofuran-3-yl)-2-oxoacetate and applied to the synthesis of a series of 7-alkoxy-2,3-dihydrofuro[2,3-d]pyridazines. Twelve pyridazines were obtained in yields of up to 70%.
Keywords: pyridazines; enones; oxoacetates; dihydrofuran; 1,4-dicarbonyl compounds; formyl esters